'Kusha' (eragrostis cynosuroids): A source of activated carbon for energy storage device. (2021) - Komal,; Kumar, Nitin; Kumar Singh, Pramod; Singh, Ranbir; Kumar Shukla, Vivek
Abstract: Activated carbon (AC) has been prepared from Eragrostis Cynosuroids, commonly known as 'kusha' grass in India. This grass is abundant in nature and may be used as a natural source for activated carbon. Activated carbon was produced by chemical activation method with zinc chloride (ZnCl2 ) on heating at 800 °C. It was demonstrated that carbonization and activation of heating of Eragrostis Cynosuroides can be carried out in two-step heating process. The structural and morphological study of the Eragrostis has been done by using X-ray diffraction and scanning electron microscopy (SEM). The electrode double layer capacitor (EDLC) was fabricated and tested by Galvanostatic charge discharge (GCD). The fabricated supercapacitor cell using the synthesized activated carbon shows specific capacitance of 88.0 Fg −1 at the current density of 1.0 Ag −1 .